Pengembangan Metode ISAKE Social Research Design - Dedy Febry Rachman; Syaiful Amri (Journal of Economic Education and Entrepreneurship Studies, 2020)
The purpose of this research development is expected to produce a product of social research methods: 1). Learning devices, 2). Learning assessment / evaluation guidelines, 3). Product social research methods, based on the identification of learning objectives by considering the curriculum that has been applied namely the development of material from the 2013 curriculum on the material "designing and conducting social research", social research methods focus on just one material, and cannot apply the same method to the material another lesson. Products that have been developed are then subjected to the process of expert validation, individual trials, small group tests and field tests. Based on these test results, social research methods are very valid, interesting, and effective can be applied in classroom learning. This can be seen from the results of the validation test with the level of product eligibility from each material expert 90%, effective products are used with an average percentage score of 91%. The results of small group product trials found 87% results and class trials were carried out after going through stages that were feasible to be applied in a classroom learning. The results of the pretest and posttest tests were found to be satisfactory with a value of 100%, which indicates that this product was able to boost student interest and learning outcomes in this case using the development product in the form of ISAKE social research methods in social research design materials. This method can also be used for a wider audience with adjustments, especially adjustments to the characteristics of students as users. Furthermore ISAKE's social research methods that have been developed can be integrated with the use of renewable information and communication technology